2007
DOI: 10.1007/s10237-007-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

Inverse method of stress analysis for cerebral aneurysms

Abstract: We present a method for predicting the wall stress in a class of cerebral aneurysms. The method hinges on an inverse formulation of the elastostatic equilibrium problem; it takes as the input a deformed configuration and the corresponding pressure, and predicts the wall stress in the given deformed state. For a membrane structure, the inverse formulation possesses a remarkable feature, that is, it can practically determine the wall tension without accurate knowledge of the wall elastic properties. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
130
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 30 publications
3
130
0
Order By: Relevance
“…These equations were initially derived for thin axisymmetric geometries [10,11], however it has been demonstrated that they can closely approximate the stress resultants in geometries that do not necessarily deform axisymmetrically due to material anisotropy [35,36] including anisotropic tissues subjected to inflation testing [19,20,37].…”
Section: Bulge Tests: Initial Estimatementioning
confidence: 99%
“…These equations were initially derived for thin axisymmetric geometries [10,11], however it has been demonstrated that they can closely approximate the stress resultants in geometries that do not necessarily deform axisymmetrically due to material anisotropy [35,36] including anisotropic tissues subjected to inflation testing [19,20,37].…”
Section: Bulge Tests: Initial Estimatementioning
confidence: 99%
“…The surface right Cauchy-Green tensor, C, and surface Green-Lagrange strains, E, were computed from the identified displacements using the local coordinate system of the NURBS mesh. The Cauchy membrane tension, t, at every Gauss point in the NURBS mesh was identified using an inverse membrane approach [5,22] which formulates the equilibrium problem directly on the deformed configuration. Additional details on the calculation of the surface strains and wall tension with respect to the NURBS coordinates can be found in [5].…”
Section: Pointwise Parameter Identificationmentioning
confidence: 99%
“…In the inverse stress computation, the boundary of the analysis domain was fixed. Enforcing displacement based boundary conditions also causes a boundary layer effect whereby the stress solution near the boundary is expected to be inaccurate [21,22]. To minimize the influence of this boundary layer on the material property identification, the outer ring of elements were excluded from the material parameter identification and any further analysis.…”
Section: Pointwise Materials Propertiesmentioning
confidence: 99%
“…Their diagnosis and the potentially dire consequences of rupture create a dilemma for patients and doctors, a dilemma centred on the risk of aneurysms growing or bleeding and amplified by the availability of minimally invasive endovascular treatments. Estimates of the incidence of aneurysmal subarachnoid haemorrhage range from 9 to 20 per 100 000 [1], considerably lower than aneurysm prevalence (3.6% at autopsy, 6.0% via angiography [2]). Thus, the majority of aneurysms do not rupture, a consistent finding in observation studies [3,4].…”
mentioning
confidence: 99%
“…Accurate mechanical models, which can predict the stress distributions in an aneurysm, have the potential to assist diagnostic decisions [6]. However, the micro-structure, material properties, thickness and the strength of the aneurysm tissue are difficult to determine non-invasively.…”
mentioning
confidence: 99%